2020
DOI: 10.1002/bco2.7
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted laparoscopic augmentation ileocystoplasty and Mitrofanoff appendicovesicostomy in children: Step‐by‐step and modifications to UChicago technique

Abstract: Objective To describe the step‐by‐step techniques and modifications for robot‐assisted augmentation ileocystoplasty and Mitrofanoff appendicovesicostomy in a pediatric population with updated institutional results. Introduction Robot‐assisted laparoscopic augmentation ileocystoplasty with Mitrofanoff appendicovesicostomy (RALIMA) protects the upper urinary tract and reestablishes continence in patients with refractory neurogenic bladder. Robotic assistance could provide the benefits of minimally invasive surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
(48 reference statements)
0
2
0
2
Order By: Relevance
“…Only one article was included in our review of the last 5 years ( 40 ), describing the experience of the American Center with RALMA technique, over a cohort of 24 patients, demonstrating a decreased post-operative pain with reduced post-operative opioid drugs, a better cosmesis, presenting a safe and feasible technique with comparable complication rates (35% of 30 day complication rate), functional and long-term outcome to the OP, with just increased operative time which can be decreased with the experience of the surgical equipe.…”
Section: Discussionmentioning
confidence: 99%
“…Only one article was included in our review of the last 5 years ( 40 ), describing the experience of the American Center with RALMA technique, over a cohort of 24 patients, demonstrating a decreased post-operative pain with reduced post-operative opioid drugs, a better cosmesis, presenting a safe and feasible technique with comparable complication rates (35% of 30 day complication rate), functional and long-term outcome to the OP, with just increased operative time which can be decreased with the experience of the surgical equipe.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent report by Adamic et al included 24 patients who underwent RAI, of which 20 patients were successfully performed using da Vinci. A series of concomitant procedures were performed, including 16 APV, 8 antegrade continence enema (ACE), and 6 bladder neck reconstruction procedures ( 35 ). These results showed that the robot offers not only the intrinsic advantages of MIS but also comparable functional outcomes to open or laparoscopic procedures.…”
Section: Distinctive Robotic Surgeries For Pediatric Patientsmentioning
confidence: 99%
“…La técnica quirúrgica de Mitrofanoff proporciona una desviación urinaria contenida que se basa en una alternativa a través del drenaje de la vejiga por medio de una apendicovesicostomía, en el cual se realiza por medio del apéndice formando un pequeño tubo o de intestino. Cuando el procedimiento realizado con el intestino es llamado Monti o ileovesicostomía (Adamic et al, 2020).…”
Section: Técnica De Abordaje Mitrofanoffunclassified
“…Las complicaciones potenciales de esta técnica implican la fuga urinaria debido a través del nuevo estroma, así como la uretra porque el paciente no está cumpliendo de manera rigurosa el programa de cateterismo (Adamic et al, 2020). La estenosis del estroma, donde existe la posibilidad que la introducción del catéter produzca dolor y la inserción sea difícil (Forster et al, 2020).…”
Section: Técnica De Abordaje Mitrofanoffunclassified